Pengaruh Personal Branding Raisa Andriana Terhadap Keputusan Pembelian Produk Raine Beauty: Survei Pada Followers Instagram @Officialrainebeauty - Annisa Az-Zahra Rahmawati; Aminah Swarnawati (Institut Nalanda, 2024)
For a public figure, personal branding needs to be considered to build credibility and have self-value, one of which is Raisa Andriana who started her career as a singer to enter the business in the cosmetics industry. The personal branding he does can be an attraction to indirectly market Raine Beauty products. Based on the said, the purpose of this research is to find out Raisa Andriana's personal branding, the purchase decision on Instagram followers @officialrainebeauty and the influence of personal branding